State-of-the-art of ultrasound-triggered drug delivery from ultrasound-responsive drug carriers. (3rd August 2022) - Fan, Ching-Hsiang; Ho, Yi-Ju; Lin, Chia-Wei; Wu, Nan; Chiang, Pei-Hua; Yeh, Chih-Kuang
ABSTRACT: Introduction: Delivering sufficient therapeutics at the target site without off-target effects is a major goal of drug delivery technology innovation. Among the established methods, ultrasound (US) with US-responsible carriers holds great promise and demonstrates on-demand delivery of a variety of functional substances with spatial precision of several millimeters in deep-seated tissues in animal models and humans. These properties have motivated several explorations of US with US responsible-responsible carriers as a modality for neuromodulation and the treatment of various diseases, such as stroke and cancer. Areas covered: We briefly discuss three specific mechanisms that enhance in vivo drug delivery via US with US-responsible carriers: 1) permeabilizing cellular membrane, 2) increasing the permeability of vessels, and 3) promoting cellular endocytotic uptake. We then reviewed the state-of-the-art materials for US-triggered drug delivery, including conventional US contrast agents, and nanocarrier formulations, such as inorganic nanoparticles and gas vesicles. Expert opinion: In this article, we summarized recent progress for each of US-responsible drug carrier, focusing on the routes of enhancing delivery and applications. The mechanisms of interaction between US-responsible carriers and US waves, such as cavitation, streaming, hyperthermia, and ROS, as well as how those interactions can improve drug release and cell/tissue uptake.